2019
DOI: 10.1038/s41598-019-42607-x
|View full text |Cite
|
Sign up to set email alerts
|

Duck production systems and highly pathogenic avian influenza H5N8 in France, 2016–2017

Abstract: In winter 2016–2017, Highly Pathogenic Avian Influenza (HPAI) H5N8 virus spread across Europe, causing unprecedented epizootics. France was massively affected, resulting in the culling of over 6 million poultry. Boosted regression tree (BRT) models were used to quantify the association between spatial risk factors and HPAI H5N8 infection in poultry holdings and to generate predictive maps for HPAI infection. Three datasets were combined to build the model: a dataset of the reported outbreaks in poultry, a data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
55
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(61 citation statements)
references
References 21 publications
6
55
0
Order By: Relevance
“…We note the risk of the domestic duck sector as a source of cryptic spread and maintenance after introduction. Our results are consistent with detailed spatial modelling during the 2016–17 HPAI 2.3.4.4b outbreaks in France [ 44 , 47 ], and previous surveillance in Bulgaria during 2008–12 [ 43 ]. Both studies found a major role for duck production systems, particularly foie gras, in the spread of avian influenza in the poultry sector.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…We note the risk of the domestic duck sector as a source of cryptic spread and maintenance after introduction. Our results are consistent with detailed spatial modelling during the 2016–17 HPAI 2.3.4.4b outbreaks in France [ 44 , 47 ], and previous surveillance in Bulgaria during 2008–12 [ 43 ]. Both studies found a major role for duck production systems, particularly foie gras, in the spread of avian influenza in the poultry sector.…”
Section: Discussionsupporting
confidence: 91%
“…Ducks often do not show clinical signs of disease, which makes identification of infection challenging. In addition, short production cycles, high movement of personnel and ducks between farms and challenges in cleaning and disinfection of transport vehicles also contribute to the potential maintenance of influenza A viruses without detection [ 43 , 47 , 48 , 49 ]. Serological and swab testing of ducks as sentinel species might be useful in predicting future outbreaks in poultry.…”
Section: Discussionmentioning
confidence: 99%
“…The increase in number of sequences will be helpful to increase the accuracy and credibility of this model. Many previous studies also have indicated domestic duck as a major source of HPAIV based on phylogenetic and epidemiological analysis (Barman et al, ; Gilbert et al, , ; Guinat et al, ; Hill et al, ; Pfeiffer, Minh, Martin, Epprecht, & Otte, ). Consistent with our data, domestic waterfowl seemed to play a major role in recent huge outbreaks of H5 HPAIVs, especially clade 2.3.4.4 H5NX HPAIVs.…”
Section: Discussionmentioning
confidence: 95%
“…The increase in number of sequences will be helpful to increase the accuracy and credibility of this model. Many previous studies also have indicated domestic duck as a major source of HPAIV based on phylogenetic and epidemiological analysis (Barman et al, 2017;Gilbert et al, 2006Gilbert et al, , 2010Guinat et al, 2019;Hill et al, 2015;Pfeiffer, Minh, Martin, Epprecht, & Otte, 2007 HPAIV had been dominant strains from 2014 and domestic ducks and geese suspected as a major source of H5N6 viruses (Bi et al, 2016). Many previous in vivo infection studies in birds showed that clade 2.3.4.4 H5NX HPAI viruses more efficiently replicated in domestic and wild waterfowl than chickens but did not induce high mortality in waterfowl Kwon et al, 2018;Pantin-Jackwood et al, 2017;Pantin-Jackwood et al, 2016;Sun et al, 2016;van den Brand et al, 2018).…”
Section: Unlike Previous Outbreaks Inmentioning
confidence: 99%
“…Avian influenza is caused by the avian influenza A virus, which occurs naturally in wild aquatic birds. Infection in poultry can cause serious damage to the global poultry market because the virus is highly contagious and has high mortality rates [1,2]. Human infections with avian influenza viruses, though rare, have been reported sporadically.…”
Section: Introductionmentioning
confidence: 99%